Розробка компонентів інформаційної системи ресторану швидкого харчування для персоналу та клієнтів - Мартинов, К. О. (ХНУРЕ, 2024)
This work is dedicated to implement components of information system of quick service restaurant for restaurant staff and clients. An implemented solution should include all the necessary functionality to meet the needs of users of system, such as creating order by client and staff, planning order queue, planning purchases of products, creating statistics of orders and other functionality according to the scope. This application should have different functionality, available for staff and clients. Creation of such a solution allows to optimize time-consuming processes and determines the direction and priorities of quick service restaurant.
Keywords: управління рестораном; інформаційна система; компоненти для персоналу; клієнтський інтерфейс; автоматизація процесів